2002
DOI: 10.1093/carcin/23.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 8-oxo-7,8-dihydro-2′-deoxyguanosine and DNA strand breaks in white blood cells of occupationally exposed workers: comparison with ambient monitoring, urinary metabolites and enzyme polymorphisms

Abstract: The relationship between biomarkers of effect (8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodGuo, HPLC system) and tail extent moment (comet assay)), markers of external and internal exposure, and biomarkers of susceptibility was evaluated for coke-oven and graphite-electrode-producing plant workers exposed to polycyclic aromatic hydrocarbons (PAHs). Mean 8-oxodGuo levels in white blood cells (WBC) of exposed workers were between 1.38 times (coke-oven, n = 20; P < 0.01) and 2.15 times (graphite-electrode-producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 42 publications
8
66
2
Order By: Relevance
“…This is in consistent with occupational studies on PAH-exposed persons, including coke oven workers (Ovrebo et al, 1998;van Delft et al, 2001;Bin et al, 2008). The results were higher than the investigations performed in West European coke oven workers which revealed lower levels of 1-OHP, not exceeding in average the concentration of 2 μmol/mol creatinine (Ovrebo et al, 1998;van Delft et al, 2001;Marczynski et al, 2002).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is in consistent with occupational studies on PAH-exposed persons, including coke oven workers (Ovrebo et al, 1998;van Delft et al, 2001;Bin et al, 2008). The results were higher than the investigations performed in West European coke oven workers which revealed lower levels of 1-OHP, not exceeding in average the concentration of 2 μmol/mol creatinine (Ovrebo et al, 1998;van Delft et al, 2001;Marczynski et al, 2002).…”
Section: Discussionsupporting
confidence: 86%
“…This may be the possible reason for GST null genotype in PAH exposure subjects (Strickland et al 1997). Further, the results might be attributable to the fact that, the lower levels of PAH exposure (Ovrebo et al, 1998;van Delft et al, 2001;Marczynski et al, 2002), exposure of the general population to PAHs may be too intermittent to be detectable with a cross-sectional design. Another possibility is that our study lacked the power to reveal the effect of AhR, CYP1A1 and GSTM polymorphisms on 1-OHP levels in the exposed group, or that these enzymes have tissue specificity for the target organs in PAH exposure subjects.…”
Section: 2699 Impact Of Ahr Cyp1a1 Gstm1 Snps On Tp53 R273g Mutatimentioning
confidence: 99%
“…In our previous study we observed significant association between GSTM1 and GSTT1 null genotypes and BMN frequencies among coal-tar population (Kumar et al, 2011). However, contrary to our results, some studies reported that CYP1A1 m1 and m2 variants did not show any effect on DNA damage among coke-oven and graphide electrode workers (Marczynski et al, 2002;Chen et al, 2006;Moretti et al, 2007). Mahimkar et al (2010) found no association of CYP1A1 gene polymorphism with MN in exfoliated buccal cells in leukoplakia patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Levels of 8-oxo-deoxyguanosine in white blood cells and DNA damage in lymphocytes were higher in coke-oven workers and graphite electrode-producing plant workers than in control subjects. The polymorphisms of the genes CYP1A1, GSTM1, GSTT1 and GSTP1 showed no association with the biomarkers of effect (Marczynski et al, 2002). Urinary 8-oxodeoxyguanosine levels were higher in 55 Taiwanese topside coke-oven workers than in 162 sideoven coke-oven workers (Wu et al, 2003).…”
Section: (E) Coke Ovensmentioning
confidence: 88%